A new chancelloriid from the Emu Bay Shale (Cambrian Stage 4) of South Australia. (3rd July 2019) - Yun, Hao; Brock, Glenn A.; Zhang, Xingliang; Li, Luoyang; García-Bellido, Diego C.; Paterson, John R.
Abstract : Chancelloria australilonga sp. nov. is described from the Emu Bay Shale (Cambrian Series 2, Stage 4) of Kangaroo Island, South Australia. The new species has a typical sac-like body, equipped with a meshwork of dozens of distinctive rosette-like sclerites. Each sclerite comprises one central ray and six or seven lateral rays, and is characterized by a pair of remarkably long and subparallel adapical rays. Chancelloria australilonga is one of the few chancelloriid species preserved with an apical orifice with an obvious peripheral tuft. The tuft consists of a series of single-rayed sclerites with inflated bases. The preservation of the specimens, coupled with sedimentological information and their general rarity in the Emu Bay Shale, suggests short-distance transport and subsequent deposition in a nearshore, low-oxygen preservational trap. Additionally, the known distribution of chancelloriids in the well-documented Konservat-Lagerstätten representing a variety of sedimentary environments, indicates that chancelloriids, especially the genus Chancelloria, were likely adapted to an extensive range of habitats. http://zoobank.org/urn:lsid:zoobank.org:pub:E46167B4-186A-4521-B3D7-DC3F48F72A30